2005
DOI: 10.1111/j.1582-4934.2005.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

A concept on the role of Helicobacter pylori infection in autoimmune pancreatitis

Abstract: Autoimmune pancreatitis, an inflammatory process of the pancreas due to an autoimmune mechanism establishing etiology of chronic pancreatitis, is characterized by the presence of autoantibodies, hypergammaglobulinemia, pancreatic enlargement, pancreatic duct strictures, and pathologic features of fibrotic changes with intense, mainly lymphocytic infiltrations, which may contribute to tissue destruction probably by apoptosis. In almost 60% of the cases, this type of pancreatitis coexists with other autoimmune d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 55 publications
2
63
0
1
Order By: Relevance
“…Only recently, however, it has been definitively shown that molecular mimicry between human and microbial antigens can be, in genetically predisposed subjects, a trigger for the onset of a large number of autoimmune diseases [11,12]. Molecular mimicry between human pancreatic autoantigens and proteins produced by Helicobacter pylori has been recently hypothesized [10], but the molecules involved have not been identified. We found that CA-II and HpCA are significantly homologous, and that the shared segments contain the binding motifs of the HLA molecule DRB1*0405, reported as a risk factor for AIP [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, however, it has been definitively shown that molecular mimicry between human and microbial antigens can be, in genetically predisposed subjects, a trigger for the onset of a large number of autoimmune diseases [11,12]. Molecular mimicry between human pancreatic autoantigens and proteins produced by Helicobacter pylori has been recently hypothesized [10], but the molecules involved have not been identified. We found that CA-II and HpCA are significantly homologous, and that the shared segments contain the binding motifs of the HLA molecule DRB1*0405, reported as a risk factor for AIP [9].…”
Section: Discussionmentioning
confidence: 99%
“…Based on an extensive review of literature, a recent paper appeared in this Journal [10] hypothesized that gastric Helicobacter pylori infection could trigger autoimmune pancreatitis through several different and probably cooperating mechanisms, including molecular mimicry between human and bacterial antigens. Prompted by this interesting theory, we aimed at identifying the potentially cross-reactive human and bacterial protein(s) using amino acid sequence comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Except for its conventional involvement in gastrointestinal diseases, Hp infection has been also implicated in a variety of extradigestive conditions, including cardiovascular, lung, hematologic, ophthalmic, skin, pancreatic, neurologic and hepatobiliary diseases (4,11,15,27) . Regarding IR-related morbidity, Hp infection may be implicated in the pathogenesis of obesity and type 2 diabetes mellitus (T2DM) (4,11,27,29) .…”
Section: Effect Of Helicobacter Pylori Eradication On Hepatic Steatosmentioning
confidence: 99%
“…Autoimmune pancreatitis accounts for 4.6-6% of all forms of chronic pancreatitis and is often associated with other autoimmune diseases, particularly Sjögren's syndrome [2]. In a recent issue of JCMM, it was proposed that Helicobacter pylori may trigger autoimmune pancreatitis through induction of autoimmunity and apoptosis [3]. This in itself was an interesting hypothesis, which centered around the idea that H. pylori has been associated with autoimmune conditions, via molecular mimicry of host structures by its constituents, which are characterized by fibrotic changes and/or lymphoplasmacytic inflammation, accompanied by aberrations of T cell apoptosis that contribute to hepatobiliary-or extrahepatic-tissue destruction.…”
mentioning
confidence: 99%
“…This in itself was an interesting hypothesis, which centered around the idea that H. pylori has been associated with autoimmune conditions, via molecular mimicry of host structures by its constituents, which are characterized by fibrotic changes and/or lymphoplasmacytic inflammation, accompanied by aberrations of T cell apoptosis that contribute to hepatobiliary-or extrahepatic-tissue destruction. Considering that H. pylori is involved in the pathogenesis and pathophysiology of these autoimmune disorders, it was proposed that this organism might trigger autoimmune pancreatitis through induction of autoimmunity and apoptosis [3,4]. This, in itself was an interesting thought.…”
mentioning
confidence: 99%